Interaction of Tyrosine-Based Sorting Signals with Clathrin-Associated Proteins - Ohno, Hiroshi; Stewart, Jay; Fournier, Marie-Christine; Bosshart, Herbert; Rhee, Ina; Miyatake, Shoichiro; Saito, Takashi; Gallusser, Andreas; Kirchhausen, Tomas; Bonifacino, Juan S. (Science (American Association for the Advancement of Science), 1995)
Tyrosine-based signals within the cytoplasmic domain of integral membrane proteins mediate clathrin-dependent protein sorting in the endocytic and secretory pathways. A yeast two-hybrid system was used to identify proteins that bind to tyrosine-based signals. The medium chains ($μ_1$ and $μ_2$) of two clathrin-associated protein complexes (AP-1 and AP-2, respectively) specifically interacted with tyrosine-based signals of several integral membrane proteins. The interaction was confirmed by in vitro binding assays. Thus, it is likely that the medium chains serve as signal-binding components of the clathrin-dependent sorting machinery.